EKSISTENSI BADAN GIZI NASIONAL DALAM SISTEM PEMERINTAHAN PRESIDENSIIL: ANALISIS FUNGSI REGULASI, EKSEKUSI, DAN PENGAWASAN - Fatkhul Muin (Yayasan Merassa Indonesia Publikasi, 2026)
he establishment of the National Nutrition Agency (BGN) as a new non-ministerial government institution has triggered a significant constitutional polemic, especially after the systemic corruption scandal in the Free Nutritious Meal (MBG) program came to light between late 2024 and mid-2025. This study aims to analyze the institutional existence of BGN within the Indonesian presidential system of government and to evaluate the overlapping functions of regulation, execution, and supervision that have led to weak internal controls. This study employs a normative legal research method with a statutory approach and a conceptual approach. Legal materials are analyzed qualitatively using descriptive-analytical techniques. The results indicate that the institutional design of BGN violates the principle of checks and balances in Constitutional Law because it concentrates functions as a policy regulator as well as a field executor (procurement of vendors/SPPG) without proportionally involving local government supervision. This centralistic character has created loopholes for abuse of power and monopolies. This study concludes that to maintain accountability in the presidential system, an institutional repositioning of BGN is required by separating regulatory functions at the central level and decentralizing execution and supervision functions to the regional level to realize clean and responsible governance